Information Technology for Food Product - T Handayani; G F Pratama (International Journal of Education, Information Technology, and Others, 2020)
Online-based businesses are increasingly prevalent because online shopping makes time and distance limitations easy to overcome. The purpose of this study is to analyze the effectiveness of information technology by creating responsive website, using in food product. The method used descriptive analysis and literatures study. With the existence of an online business, marketing food products are easier and open up very promising opportunities. The results achieved can get information on the average price of products in the market. To compete with others, it can make food products more creative to attract the attention of buyers and can expand the reach of marketing.